PREVALENCE OF ANGLE-CLOSURE DISEASE IN A RURAL SOUTHERN PUNJAB POPULATION (Journal of Medical & Health Sciences Review, 2025)
Objective: To determine the prevalence, risk factors, and awareness of angle-closure disease in a rural population of Southern Punjab, Pakistan.Methods: A population-based, cross-sectional study was conducted among adults aged ≥40 years from randomly selected clusters in rural Southern Punjab. Participants underwent a comprehensive ophthalmic examination including gonioscopy, intraocular pressure measurement, optic disc assessment, and anterior segment optical coherence tomography (AS-OCT). Diagnosis followed a modified International Society of Geographical and Epidemiological Ophthalmology classification.Results: Of 6,240 eligible individuals, 5,812 participated (response rate: 93.1%). The prevalence of primary angle-closure suspect (PACS), primary angle closure (PAC), and primary angle-closure glaucoma (PACG) was 5.2%, 2.4%, and 1.9%, respectively. Nearly one in ten adults (9.5%) had some form of angle-closure pathology. Female sex was a strong independent risk factor for PACG (adjusted odds ratio [aOR]: 2.10, 95% CI: 1.44-3.08), with prevalence significantly higher in women (2.5%) than men (1.3%). Prevalence increased markedly with age, from 0.6% in 40-49-year-olds to 4.8% in those ≥70 years (aOR: 4.50). Hyperopia (aOR: 3.80) and shorter axial length (aOR per 1 mm decrease: 2.50) were significant biometric risk factors. Awareness was critically low; only 12.1% of the population had heard of glaucoma, and 96.4% of PACG cases were previously undiagnosed.Conclusion: Rural Southern Punjab is a hyperendemic region for angle-closure disease, characterized by an exceptionally high prevalence, significant female and elderly preponderance, and a devastating lack of awareness and diagnosis. Urgent public health interventions for targeted screening and treatment are needed to prevent widespread blindness.